Regional Economic Issues, November 2015, Europe. (Regional Economic Outlook, 2015)
The key policy challenges facing countries in Central, Eastern, and Southeastern Europe remain broadly unchanged, among them supporting domestic demand, addressing financial crisis legacies, rebuilding buffers against external shocks, and improving the business environment. Country-specific priorities depend on how far along they are in the postcrisis adjustment and their exposure to external risks.